INTEGRATED MARKETING COMMUNICATION: A LITERATURE REVIEW - Said Ma’ruf; Anwar (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
The concept of Integrated Market Communication relates to marketing communication planning and highlights the benefits of having a comprehensive plan that assesses the strategic roles of different communication disciplines, including public relations, advertising, direct marketing, and sales promotion. By combining these disciplines, the plan can maximize communication impact and clarity. The notion of integrated marketing communication aims to plan, create, consolidate, and implement many marketing communication benches. These benches include advertising, sales, promotion, publicity hubs, and direct marketing. Using a literature review approach, this research highlights some related previous studies as well as available relevant literature to get a deep understanding and meaningful insight about IMC. The review result shows that among the effective IMC strategies assist companies in marketing their products and services by sending out complimentary, understandable signals that are ultimately intended to turn prospects into consumers. In addition, it recommends that marketing managers consider the six Ms: market, mission, message, media, money, and measurement while developing an IMC plan.